Co-authorship networks of scientific elite: case study of information science in Croatia - Pečarić, Đilda; Tuđman, Miroslav (2016)
Relatively small number of scientists receives large number of citations. Researches of most cited authors who form scientific elite are often. What is rare are researches of co-authorship of most cited authors. In this paper we research co-authorship networks of most cited authors in information science in Croatia. Overview of social characteristics of co-authorship networks or whether authors and co-authors belong to the university or research institute is given. Also, position of most cited authors in co-authorship networks is researched: a) order of co-authors and their position in the scientific elite according to time periods ; b) the institutional affiliation ; c) international collaboration. We try to use bibliometric methods for detecting, identifying and visualizing social, institutional and intellectual networks and impact of scientific elite
Projekt MZOS
ENG